Loyalty to influencers and brands: Does negative publicity matter? - Bari, Andriansyah; Angguna, Welan Mauli; Izzati, Astika Ulfah; Anindea, Frianka (Journal of Innovation in Business and Economics, 2024)
This study examines the critical role of trust in influencer marketing, focusing on how influencers' expertise, authenticity, and homophily affect followers' trust and subsequently their loyalty to influencers and brands. Utilizing an explanatory quantitative cross-sectional non-experimental design, data were collected from 202 consumers who purchased products such as cosmetics, skincare, and gadgets after watching influencer reviews. The data were analyzed using structural equation modeling (SEM). The results indicate that authenticity, expertise, and homophily significantly contribute to building trust among followers, with authenticity being the most influential factor. Meanwhile, physical attractiveness does not significantly impact trust. Furthermore, trust serves as a crucial mediator, enhancing the effects of influencers' expertise, authenticity, and homophily on both influencer and brand loyalty. Interestingly, negative publicity does not significantly moderate the relationship between trust and loyalty, suggesting that cultural and emotional factors in the Indonesian context may mitigate its impact.